TINJAUAN HUBUNGAN PLASTIK HDPE DENGAN TONGKOL JAGUNG UNTUK PEMBUATAN BATAKO KOMPOSIT - Vidi Akhmad Rifa’i; Hermansyah; Eti Kurniwati (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2020)
Plastic is one of the most commonly used materials today. However, the continuous use of plastic has the potential to cause problems in the future. Because, plastic waste takes a very long time to be able to decompose on the ground. If it is dumped on the ground, it will damage groundwater and soil quality. Therefore, plastic waste must be managed properly, so as not to damage the environment. On the other hand, Sumbawa Island is one of the biggest corn-producing islands in Indonesia. It is unfortunate if the waste in the form of corncobs is not utilized properly. In addition to the problem of plastic and corncob waste, Indonesia also has problems with geographic areas. The problem of this research is how to utilize plastic waste and corncob waste into earthquake resistant building blocks. So, it is expected to be able to replace bricks, bricks, or furniture in order to minimize environmental damage. The data needed in this study were obtained from several scientific papers related to this research. From these data then analyzed to obtain the right formula for making composite bricks and testing. Tests conducted on this product are specific gravity, water absorption, and heat resistance. As a comparison, hebel is also included in each test.